The content and essence of aphorisms by Ayteke bi, the great Kazakh orator - Urkinbayeva , Maqpal (The Lingua Spectrum, 2025)
Ayteke bi is a great personality who paid special attention to the fate of the Kazakh people. Ayteke bi was a charismatic orator, a leader who knew how to manage people, and a sage who attracted the people and society to himself. Ayteke bi was known for his wisdom, justice, and oratory skills. His aphorisms, wise words have been passed down from mouth to mouth for centuries, becoming part of the spiritual heritage of the Kazakh people. This article is devoted to analyzing the content and essence of Ayteke bi’s aphorisms.